2015 IEEE 16th International Symposium on a World of Wireless, Mobile and Multimedia Networks (WoWMoM) 2015
DOI: 10.1109/wowmom.2015.7158134
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive broadcast suppression for Trickle-based protocols

Abstract: Low-power wireless networks play an important role in the Internet of Things. Typically, these networks consist of a very large number of lossy and low-capacity devices, challenging the current state of the art in protocol design. In this context the Trickle algorithm plays an important role, serving as the basic mechanism for message dissemination in notable protocols such as RPL and MPL. While Trickle's broadcast suppression mechanism has been proven to be efficient, recent work has shown that it is intrinsi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…It does so by counting the number of consistent messages that are received within a specific window and, then, when such a number surpasses a preconfigured redundancy constant (k), it suppresses any further propagation of such received messages. However, studies have reported that the optimal setting of the redundancy constant is not a trivial task and relies greatly on the application scenario, in addition to that some issues may emerge if configured incorrectly [118] [120]. For instance, it was shown in [118] that, if the redundancy constant is not configured correctly, the suppression mechanism might result in sub-optimal routes, especially in heterogeneous topologies with regions of different densities.…”
Section: ) Suppression Mechanism Inefficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…It does so by counting the number of consistent messages that are received within a specific window and, then, when such a number surpasses a preconfigured redundancy constant (k), it suppresses any further propagation of such received messages. However, studies have reported that the optimal setting of the redundancy constant is not a trivial task and relies greatly on the application scenario, in addition to that some issues may emerge if configured incorrectly [118] [120]. For instance, it was shown in [118] that, if the redundancy constant is not configured correctly, the suppression mechanism might result in sub-optimal routes, especially in heterogeneous topologies with regions of different densities.…”
Section: ) Suppression Mechanism Inefficiencymentioning
confidence: 99%
“…The work in [120] highlighted the ambiguity associated with configuring the redundancy parameter, k, in RPL networks. For instance, the Trickle RFC [69] states that typical values for k are 1-5, whereas the RPL RFC [14] sets the value 10 as the default value.…”
Section: ) Suppression Oriented Enhancementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumes d is known which is usually the case in the MAC layers of wireless networks. In [20], the authors use a similar approach with k = α * c, where c can be seen as an approximation of the node degree. The value c is dynamically computed from scratch for each interval and adjusted within the interval.…”
Section: Related Workmentioning
confidence: 99%
“…Each node runs Trickle to reach a consistent state with its neighbors with the same parameters I min and I max . As in [3,4] and [20], we assume that the redundancy constant k is not necessarily the same on all nodes. The network is assumed to be in steady-state, i.e., I = I max , all nodes are consistent, and no node triggers a Trickle reset because of external events.…”
Section: Trickle's Unfairnessmentioning
confidence: 99%